Early cognitive decline in Creutzfeldt-Jakob disease associated with human growth hormone treatment. Issue 10 (20th October 2003) - Cordery, R J; Hall, M; Cipolotti, L; Al-Sarraj, S; O'Donovan, D G; Davidson, L; Adlard, P; Rossor, M N
Abstract : Background: Most cases of Creutzfeldt-Jakob disease (CJD) in recipients of human cadaveric growth hormone present with a cerebellar syndrome. Dementia is thought to occur late and as a minor feature of the illness. However, neuropsychology data published on these cases are largely qualitative and anecdotal. The first published case does include a neuropsychological assessment seven months after the onset of a cerebellar syndrome, showing evidence of intellectual decline. Subsequent reports hint that cognitive problems may be present in the initial stages of the illness. Objective: To assess early cognition in Creutzfeldt-Jakob disease in recipients of pituitary derived human growth hormone. Methods: Detailed neuropsychology assessment is reported at referral (mean 4.5 months from the onset of symptoms; range 4 to 6 months) in five patients with histologically proven human growth hormone derived CJD. Results: All cases presented with a cerebellar syndrome and only one had noticed mild memory problems. On formal testing, however, four had demonstrable mild intellectual decline, as measured on the WAIS-R. One case showed selective visual memory impairment and frontal executive dysfunction. Conclusions: These findings suggest that, although not the presenting feature, mild cognitive decline may be evident in the early stages of CJD associated with human cadaveric growth hormone treatment.